Strategi Komunikasi Pemasaran di Syirkah Aqiqah Surabaya - Ulandhari Ulandhari; Lilik Hamidah (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2019)
This article examines the marketing communication strategy at Syirkah Aqiqah Surabaya. The purpose of this research is to identify the marketing communication strategy carried out by syirkah aqiqah in marketing its products. This study uses a qualitative-descriptive approach to understand the phenomena that occur thoroughly and deeply. The results of this study are the marketing communication strategies used by syirkah aqiqah to market and introduce their products including (1) Syirkah Aqiqah using the Word of Mouth, (2) Syirkah Aqiqah making attractive packaging, (3) Syirkah Aqiqah giving discounts and free one bottle of Syuniz. to create sales promotions, and (4) Syirkah Aqiqah uses interactive marketing or online marketing through Instagram and Facebook.